An examination of imagery used to represent fundamental British values and British identity on primary school display boards (UCL Press, 2019)
It is observable that display boards are being applied widely by primary schools as visual representations for teaching and learning about the stated fundamental British values of democracy, the rule of law, individual liberty and the mutual respect and tolerance of those with different faiths and beliefs. The research presented by this article is based upon analysis of 27 display boards from primary schools across England, including findings from in-depth interviews with three primary school teachers. We wanted to identify and to understand how discourses of British national identity such as monoculturalism and multiculturalism are reified by schools and teachers through the imagery used on primary school display boards in the representation of fundamental British values. Our research makes an original contribution to the debate on teaching and learning about national identity, by offering empirical evidence both of representations of fundamental British values and of teacher interpretations of the policy.